Explaining diversity in the worldwide diffusion of codes of good governance - Haxhi, Ilir; van Ees, Hans (Journal of International Business Studies, 2010)
Extending earlier literature on diffusion of codes of good governance (CGGs) by integrating the effect of national culture, this study offers a novel perspective on cross-national diversity in the worldwide diffusion of corporate governance best practices. We argue that particular cultural dimensions affect the indicators (i.e., total number of codes per country and identity of issuing organizations) of such diffusion. For a sample of 67 countries our analysis reveals that individualist cultures have a stronger tendency to develop CGGs. In cultures with a high receptivity to power differences there is a higher probability that the first issuers are the government, directors’ or professional associations; whereas with low receptivity, the stock exchange and investors’ groups of issuers are more likely to initiate the first code. The effects of culture remain significant even after accounting for differences in legal systems and economic institutions, indicating that national culture may serve as a comprehensive indicator of the regulatory stance with respect to good governance. Indeed, the effect size is large enough to give pause (e.g., to a location choice), and possibly has relevance for strategic decision-making by international companies.